2010
DOI: 10.1002/adma.201000278
|View full text |Cite
|
Sign up to set email alerts
|

Supersensitive, Fast‐Response Nanowire Sensors by Using Schottky Contacts

Abstract: A Schottky barrier can be formed at the interface between a metal electrode and a semiconductor. The current passing through the metal-semiconductor contact is mainly controlled by the barrier height and barrier width. In conventional nanodevices, Schottky contacts are usually avoided in order to enhance the contribution made by the nanowires or nanotubes to the detected signal. We present a key idea of using the Schottky contact to achieve supersensitive and fast response nanowire-based nanosensors. We have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
224
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(233 citation statements)
references
References 29 publications
8
224
1
Order By: Relevance
“…Nanomaterials can be fabricated directly on MEMS devices [9], [30]. Presynthesized nanomaterials were also transferred onto MEMS devices via dielectrophoresis trapping [12], [22], [31], focused-ion-beam deposition [14], and direct pick and place [11], [13], [17], [20], [32]- [35]. Due to the flexibility of pick-and-place nanomanipulation inside SEM and no need for nanomaterial preprocessing (e.g., sonication), we transferred individual silicon nanowires from growth substrates onto MEMS devices via direct pick and place.…”
Section: B Transfer Of Nanowire Onto Mems Devicementioning
confidence: 99%
“…Nanomaterials can be fabricated directly on MEMS devices [9], [30]. Presynthesized nanomaterials were also transferred onto MEMS devices via dielectrophoresis trapping [12], [22], [31], focused-ion-beam deposition [14], and direct pick and place [11], [13], [17], [20], [32]- [35]. Due to the flexibility of pick-and-place nanomanipulation inside SEM and no need for nanomaterial preprocessing (e.g., sonication), we transferred individual silicon nanowires from growth substrates onto MEMS devices via direct pick and place.…”
Section: B Transfer Of Nanowire Onto Mems Devicementioning
confidence: 99%
“…To realize ZnO-based UV photodetectors with high sensitivity and fast response time, a Schottky contact instead of an ohmic contact was adopted [107,[112][113][114][115]. For example, Zhou and coworkers fabricated a Schottky junction-type photodetector that used ZnO nanowire and Pt metal electrode to form Schottky contact [98].…”
Section: Photodetectorsmentioning
confidence: 99%
“…In earlier work, different materials have been used as photoconductive device e.g. MoS 2 [1], Si [3], ZnO [9], Bi 2 S 3 [10], InP [11], CdS [12] etc. It is reported that these material can give substantial photoconductive gain using Schottky contact where they have been used as single nanowire device.…”
Section: Introductionmentioning
confidence: 99%
“…Nanotubes, nanowires and nanobelts are important one-dimensional (1D) nanomaterials that are the foundation for nanoscience and nanotechnology [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Novel nanoscale optoelectronic devices are important applications of nanomaterials, particularly nanowires which can be scaled down to a single nanowire (NW) device [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation